The impacts of patient mistreatment on healthcare workers' role behaviors: a study in Chinese Fangcang shelter hospitals - Wei Yan; Na Bao; Shuangjiang Zheng; Huan Wang; Dongmei Yue; Li Chen (BMC, 2023)
Abstract Background Fangcang shelter hospitals have played an important role in the battle against the COVID-19 epidemic in China. Patients' verbal and physical attacks on medical workforce are prone to occur in such hospitals. This study explored the impacts of patient mistreatment on healthcare workers' role behaviors (service performance and patient-oriented organizational citizenship behavior). Methods We examined the influence of patient mistreatment on service performance and patient-oriented organizational citizenship behavior, as well as the mediating effect of emotional exhaustion and the moderating effect of displaced aggression by patients, using hierarchical linear regression and conditional process analysis. Results Patient mistreatment was positively associated with emotional exhaustion among healthcare workers, while emotional exhaustion was negatively associated with service performance and patient-oriented organizational citizenship behavior. Mediation analysis revealed that emotional exhaustion mediated the association between patient mistreatment and both types of role behaviors. Moderated mediation analysis found that the mediation effect was weaker when the displaced aggression by patients was high. Conclusions The findings clarified the relationship among patient mistreatment, emotional exhaustion, service performance, and patient-oriented organizational citizenship behavior. Additional assistance should be provided to healthcare workers dealing with patient mistreatment. Displaced aggression by patients attenuates the positive effects of patient mistreatment on the emotional exhaustion of healthcare workers. Our findings reveal the mechanism and boundary conditions of patient mistreatment affecting healthcare workers' service performance and patient-oriented organizational citizenship behavior.